Rotating-Magnetic-Field-Assisted Electrodeposition of Copper for Ambulance Medical Equipment - Syamsuir Syamsuir; Ferry Budhi Susetyo; Bambang Soegijono; Sigit Dwi Yudanto; Basori Basori; Maman Kartaman Ajiriyanto; Daniel Edbert; Evi Ulina Margaretha Situmorang; Dwi Nanto; Cahaya Rosyidan (Universitas Muhammadiyah Magelang, 2023)
This study examines the influence of the application of a rotating magnetic field in the electrodeposition of copper (Cu). During the electrodeposition, five constant magnets were rotated (500 and 800 rpm) towards the bottom of the sample. To investigate deposition rate, surface morphology, phase, structure, corrosion resistance, and hardness in deposited Cu using a weighing scale, a scanning electron microscope equipped with energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD), potentiodynamic polarization, and hardness tester respectively. Bacterial activity was also evaluated through this research. Morphological surface observations showed that the increase in the rotational speed of the magnets during the electrodeposition process led to a smooth surface. A perfect Cu phase covers Al alloy with no oxide. The potentiodynamic polarization demonstrated by the increase in the rotating led to a shift to the more positive value of the corrosion potential. Moreover, the corrosion current also decreases with the increase in the rotating speed of the magnets. Less crystallite size promoted forming a higher hardness and inhibition zone of the Cu films.